Applications of Gas Chromatography (IntechOpen, 2021)
This valuable book aims to provide a connection between various chromatography techniques and different processes. Authors applied these techniques in supercritical technology, medical, environmental, physique and chemical processes. Most of them prepared mathematical support (such as correlation) for their original results obtained from the chromatography techniques. Since chromatography techniques (such as GC, HPLC & etc) are separating and analyzing methods, this chapters will help other researchers and young scientists to choose a suitable chromatography technique. Furthermore, this book illustrates the newest challenges in this area.